2014
DOI: 10.3801/iafss.fss.11-1393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size on Pyrolysis Kinetics of Forest Fuels in Nitrogen

Abstract: Pyrolysis of forest combustibles is an elementary process in the ignition and spread of forest fires, and particle size is an important parameter which affects the pyrolysis kinetics. In this work, samples of pine needle (PN), pine branch (PBr) and pine bark (PB) were subject to thermogravimetric experiments, in order to examine the effect of particle size on pyrolysis characteristics. For all the samples, one peak and two shoulders are observed in all of the mass loss curves, at different positions for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
3
10
1
1
Order By: Relevance
“…The experimental thermokinetic parameters of forest fuel decomposition in inert and oxidizing media at varying particle sizes are given in Tables 1 and 2. Table 1 shows that the larger is the particle size, the higher the activation energy and the pre-exponential factor are for second and third areas (similar results were obtained in [13]). It is very propable that the intensity of interaction of particles with an oxidizing agent (oxygen) decreases with an increase in their size.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The experimental thermokinetic parameters of forest fuel decomposition in inert and oxidizing media at varying particle sizes are given in Tables 1 and 2. Table 1 shows that the larger is the particle size, the higher the activation energy and the pre-exponential factor are for second and third areas (similar results were obtained in [13]). It is very propable that the intensity of interaction of particles with an oxidizing agent (oxygen) decreases with an increase in their size.…”
Section: Resultssupporting
confidence: 75%
“…It was concluded that the samples with a particle size of less than 0.5 mm were the most reactive. The characteristics of the FF components (such as density and particle size) were proved to influence the rate of physical and chemical processes and play an important role in predicting conditions and characteristics of FF burning [3,12,13]. It was concluded that in this regard, the study of thermokinetic characteristics of components close to forest cover is necessary for mathematical modeling of forest fire propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the activation energies obtained for timber (PR and EM) are quite close to the values reported in the literature for similar species under similar conditions. The activation energies obtained for Australian pine litters PB, PT, and PN in this study have a higher value than those reported by Korobeinchev et al 2013 [30] for Siberian Pine forest litters in an inert atmosphere of helium. The authors also observed that the activation energy varied with conversion and spanned from 150 to 400 kJ/mol in the pyrolysis range.…”
Section: Fig 2: Ftir Spectroscopy Of Both Pr and Em Timber And Forescontrasting
confidence: 50%
“…However, for the litter materials, the activation energies do vary with conversion in the range of the pyrolysis reaction which suggests a multi-step reaction model should be used. A multi-step reaction model, in this case, would correspond to a single reaction model for the decomposition of each of cellulose, hemicellulose, and lignin [30].…”
Section: Fig 2: Ftir Spectroscopy Of Both Pr and Em Timber And Foresmentioning
confidence: 99%
“…Bir başka deyişle, yapılan çalışmalar partikül boyutundaki artışın (75-150 µm → 150-250 µm) aktivasyon enerjisinde de artışa neden olduğunu göstermiştir. Benzer durum, Niu ve Liu'nun çalışmasında [41] çam ağacı dalları ve çam ağacı kabukları için partikül boyutunun 75-150 µm'den 150-300 µm'ye çıkarılmasında da gözlenmiştir. Suriapparao ve Vinu da [42], ağaç talaş tozunun sekiz farklı partikül boyutunun (26,5-925 µm) yavaş piroliz kinetiğini inceledikleri çalışmalarında, düşük ısıtma hızlarında (5, 10 ve 20 °C/dk) partikül boyutundaki artış ile aktivasyon enerjisinde artış gözlediklerini raporlamışlardır.…”
Section: Model Içermeyen Kinetik Yöntem Ile Yapılan Hesaplamalarunclassified